2009
DOI: 10.1007/s10528-009-9316-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation Crosses, Inheritance Study, and Genetic Variability in the Brown Planthopper Complex, Nilaparvata lugens (Homoptera: Delphacidae)

Abstract: Studies on hybridization, inheritance, and population genetics of brown planthoppers that infest rice and weeds were undertaken using starch gel electrophoresis to determine whether the weed-infesting population represents a biological race or a species. F(1) and F(2) generations were produced by crosses between parental insects from the two populations with little indication of hybrid sterility. Gpi, Mdh, and Idh loci were inherited in a simple Mendelian fashion in families of two sympatric populations. Sixte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…In addition to the apparent genetic differences between insect biotypes, several indications of associations between secondary symbionts and biotype populations in insects, particularly whitefly and aphid, have been reported (4,37). Previous studies have detected biological differences among N. lugens biotype populations (6,25,36). The three biotypes of N. lugens were maintained on specific rice varieties for a long time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the apparent genetic differences between insect biotypes, several indications of associations between secondary symbionts and biotype populations in insects, particularly whitefly and aphid, have been reported (4,37). Previous studies have detected biological differences among N. lugens biotype populations (6,25,36). The three biotypes of N. lugens were maintained on specific rice varieties for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…In N. lugens, the biotype is assigned to a population with the ability to damage varieties of rice that carry resistance genes and that were previously resistant to it (5). It has been claimed that some biotypes of N. lugens differ in small morphological features, isozymes, and DNA polymorphisms (6,25,36). However, the precise nature of the virulence-conferring mechanisms in N. lugens biotypes (and their modes and stability of inheritance) is not clear.…”
mentioning
confidence: 99%
“…The analyses of isozymes and RAPD-PCR markers indicated that BPH captured from rice plant has high esterase activity compared to BPH captured from L. hexandra and they represent two distinct closely . related sibling species in Malaysia [14,15]. Latif et al [16] reported that Direct amplified length polymorphism (DALP) also useful for the analysis of genetic polymorphisms in brown plant hopper, N. lugens populations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on nymphal survival, virulence, ovipositional preference, mate choice, and hybridization experiments, Claridge et al [5] suggested that the rice and Leersia infesting populations of brown planthopper (BPH) represented two distinct sympatric biological species. In recent studies, the analyses of isozymes and RAPD-PCR markers indicated that BPH with high esterase activity usually captured from rice plant, and those with low esterase activity usually captured from L. hexandra in Malaysia represent two distinct closely related sibling species [6, 7]. …”
Section: Introductionmentioning
confidence: 99%